PS-P14-9: SALT CONTENT IN COMMONLY CONSUMED PROCESSED PACKAGED FOODS AND THEIR CONFORMITY WITH LABEL INFORMATION IN BANGLADESH. (January 2023) - Sobhan, Sheikh Mohammad Mahbubus; Mamun, Mohammad Abdullah Al; Bahar, Nisarga; Sarwar, Sneha; Ashraf, Md Musharraf; Abedin, Md Joynul; Karim, Md Rizwanul; Alim, Md Abdul; Ahmed, Jasimuddin; Shamim, Abu Ahmed; Shaheen, Nazma; Amin, Mohammad Robed; et al.
Abstract : Objective: Consumption of processed foods is surging in low and middle-income countries and gradually replacing home-cooked meals. Unfortunately, the salt content is usually high in these processed foods which eventually causes hypertension, heart diseases and stroke. As the reduction of overall salt intake serves as a preventive measure for Non-communicable Diseases, so, the present study was undertaken to estimate the content of salt in commonly consumed processed foods in Bangladesh and to assess their conformity with label declaration. Along with salt, total sugar, total fat, saturated fat, trans fat, protein, fiber and energy were also assessed. Design and Methods: It was a cross-sectional population-based study. A total of 11 most consumed processed packaged foods were identified from the 8 administrative divisions of Bangladesh through a household survey (n = 480) and a market survey (n = 24) done in 2019. Samples from all the 8 divisions were collected following a list of commonly consumed foods and brands. The foods included for analysis were chips, chanachur, fried peas, pulse, noodles, biscuits, lozenge/lollipop, milk chocolate, chutney, and ice cream. A brand-wise composite sample of each processed food item was prepared by pooling at least 12 samples in the Institute of Nutrition and Food Science. Samples were analyzed by 'Association of Official Analytical Chemists' and titrimetric method (IS-1743) method at an accredited lab. The healthiness of the products was evaluated in terms of the Health Star Rating scheme of Australia and the UK traffic light labelling system. Label information was compared with corresponding analytical values and per cent variation was calculated. Results: Most of the analyzed foods contained excessive amounts of salt, sugar and saturated fat. Alarmingly, for salt, where WHO labels '> 1.5 g/100g' as 'High/Excessive' the products range from 4 g to 0.14 g per 100 g. Among them, 8 out of 11 food items were red marked. None of the brands qualifies for health claims in the star rating scheme and the UK traffic light system due to high content of salt and other critical nutrients. Most of the products misreported the nutrient content on labels. Conclusions: For the sake of public health, modification is highly needed in the processing of commonly consumed processed foods to make them healthy and less salt-containing. Study findings strongly advocate the necessity for strict regulations for appropriate user-friendly nutritional labelling. These measures will help in attaining Sustainable Development Goal 3-the health targets.